2014
DOI: 10.1002/2013ja019476
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and observation of spacecraft plume/ionosphere interactions during maneuvers of the space shuttle

Abstract: This work employs in situ measurement data and constructive simulations to examine the underlying physical mechanisms that drive spacecraft plume interactions with the space environment in low-Earth orbit. The study centers on observations of the enhanced flux of plasma generated during a maneuver of Space Shuttle Endeavour as part of the Sensor Test for Orion Relative Navigation Risk Mitigation experiment in May 2011. The Canary electrostatic analyzer (ESA) instrument mounted on the portside truss of the Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, in practical applications, it is found that the electric thruster plume will bring great harm to the spacecraft, and even lead to spacecraft failure. For example, Charge Exchange (CEX) ions of the plume can bring thermal loads and pollute electronic components of the spacecraft (1)(2)(3) . Therefore, how to reduce the impact of the plume on the spacecraft is critical to the future application of electric thrusters.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practical applications, it is found that the electric thruster plume will bring great harm to the spacecraft, and even lead to spacecraft failure. For example, Charge Exchange (CEX) ions of the plume can bring thermal loads and pollute electronic components of the spacecraft (1)(2)(3) . Therefore, how to reduce the impact of the plume on the spacecraft is critical to the future application of electric thrusters.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 This methodology has also been applied to the Space Shuttle rocket plume expansion into the ionosphere to explain the correlation between rocket firings and measured ion fluxes aboard the international space station (ISS). 4 Several others [5][6][7] have also investigated the interactions between spacecraft, rocket plumes, and the space environment, but are focused on interactions at LEO. The lower densities, higher energies of ambient ions, and lower geomagnetic field strength at GEO relative to LEO changes the relative importance of the various plume-atmosphere interactions, and therefore a separate analysis is required to better understand and predict plume behavior at GEO.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating these effects is critical for capturing the development of the spacecraft plume in the plasma environment, particularly over large distances. Recent efforts [ Stephani and Boyd , ; Stephani et al , ] investigating spacecraft plumes in low Earth orbit (LEO) have demonstrated that interaction of the spacecraft neutral plume with the ambient plasma forms a relatively high‐density spacecraft ion plume. The propagation of this ion plume is determined primarily by the interaction with the magnetic field, but the development of the neutral spacecraft plume is also affected (albeit indirectly) by the magnetic field interaction owing to secondary charge‐exchange reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The present study aims to examine the interaction between spacecraft hydrazine thruster plumes and the ambient magnetosphere in geostationary Earth orbit (GEO) conditions. While previous efforts have developed a combined direct simulation Monte Carlo/particle‐in‐cell (DSMC/PIC) methodology to examine plumes in LEO [ Stephani and Boyd , ; Stephani et al , ], this study focuses on the additional physical model considerations involving nonequilibrium plasma mixtures. The rarefied nature of the magnetosphere, as well as the presence of the surrounding plasma environment, requires the use of a combined DSMC/PIC methodology, which is detailed next.…”
Section: Introductionmentioning
confidence: 99%